2010
DOI: 10.1038/hr.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor kinase 4 gene variants are not associated with preeclampsia in Northern Han Chinese

Abstract: Genetic variations in preeclampsia (PE) may affect PE risk. The G protein-coupled receptor kinase 4 (GRK4) gene encodes a member of the Ser/Thr protein kinase family and has been linked to both genetic and acquired hypertension. The aim of this study was to investigate the association between polymorphisms (T-rs1024323-C and T-rs1801058-C) in GRK4 and PE in Northern Han Chinese. Using a case-control design, the association between the GRK4 exon-4 T-rs1024323-C and exon-13 T-rs1801058-C polymorphisms and the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A recent metaanalysis showed that GRK4 and DRD1 gene polymorphisms, rs1024323 GRK4 (OR = 1.826) and rs4532 of DRD1 genes (OR = 1.833), are associated with hypertension in Caucasians and East Asians, respectively [59]. GRK4 polymorphisms are not associated with preeclampsia in northern Han Chinese [147]. However, DRD1 (−48G) and DRD4 (−521T) receptors are associated with preeclampsia in a Polish population [148].…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%
“…A recent metaanalysis showed that GRK4 and DRD1 gene polymorphisms, rs1024323 GRK4 (OR = 1.826) and rs4532 of DRD1 genes (OR = 1.833), are associated with hypertension in Caucasians and East Asians, respectively [59]. GRK4 polymorphisms are not associated with preeclampsia in northern Han Chinese [147]. However, DRD1 (−48G) and DRD4 (−521T) receptors are associated with preeclampsia in a Polish population [148].…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%